Microstructural and mechanical characterization of HSLA X70 Welded joints using eddy current testing (ECT). Issue 1 (1st April 2022) - Bensaid, N.; Benlamnouar, M. F.; Badji, R.; Saadi, T.; Zidani, M.; Gousmine, M.
Abstract: This paper proposes an approach for measuring the mechanical properties by non-destructive testing techniques using eddy current testing (ECT), for a welded and heat-treated microalloyed material (X70) dedicated to hydrocarbon transport. This study offers a new measurement method based on linear approach, to expect mechanical property in microstructures by using Non-destructive testing (ECT) that can apply to mechanical systems, materials, weldments, etc. The result show that hardness measurements are in broad have the same trend with impedance function which depend of heat treatment variable applied to weld joint.